Bhāgavata Across Boundaries. (27th July 2018) - Hawley, John Stratton
Abstract: If one takes a broad view of the term 'translation', one might trace the phenomenon of translating the Bhāgavata Purāṇa into Brajbhasha as far back as the sixteenth century. Around the beginning of the eighteenth century, however, the author of the Bhāgavata Māhātmya seems to want to put constraints on this liberal vernacularising enterprise, even while court painters in Udaipur were expanding it further by translating the Sūrsāgar into visual art. One can think of these acts of translation, interpretation, and control as offshoots of the Bhāgavata' s own journey through history, or one might equally think of them as constituting aspects of a stream of cultural and religious events in which the Sanskrit text is just one element. To take the latter view is not only to place the Bhāgavata in a somewhat wider field than we often do, but to ask how it managed to retain its perceived status as Urtext— if it did—in the presence of considerable popular activity in the performing and visual arts.